2015
DOI: 10.1093/jnci/djv394
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reactive Oxygen Species in the Abrogation of Oxaliplatin Activity by Cetuximab in Colorectal Cancer

Abstract: Background:The antibody cetuximab, targeting epidermal growth factor receptor (EGFR), is used to treat metastatic colorectal cancer (mCRC). Clinical trials suggest reduced benefit from the combination of cetuximab with oxaliplatin. The aim of this study was to investigate potential negative interactions between cetuximab and oxaliplatin.Methods:Thiazolyl blue tetrazolium bromide (MTT) assay and Calcusyn software were used to characterize drug interactions. Reactive oxygen species (ROS) were measured by flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 41 publications
3
45
1
Order By: Relevance
“…Collectively, these results indicated that GSR Thr507 is most likely the inducible phosphorylation substrates of AMPKα1 in CRC cells under glucose deprivation and that it plays critical roles in GSR activity and likely functions accounting for the protective roles of AMPKα1 in cell survival under nutrient stress. AMPKα1 is a potential target in CRC Chemotherapeutic agents were previously reported to induce redox stress in cancer cells [20]. We therefore hypothesized that knockdown of AMPKα1 could sensitize CRC cells to oxaliplatin treatment.…”
Section: Ampkα1 Maintains Ros At Low Levels Through the Regulation Ofmentioning
confidence: 98%
“…Collectively, these results indicated that GSR Thr507 is most likely the inducible phosphorylation substrates of AMPKα1 in CRC cells under glucose deprivation and that it plays critical roles in GSR activity and likely functions accounting for the protective roles of AMPKα1 in cell survival under nutrient stress. AMPKα1 is a potential target in CRC Chemotherapeutic agents were previously reported to induce redox stress in cancer cells [20]. We therefore hypothesized that knockdown of AMPKα1 could sensitize CRC cells to oxaliplatin treatment.…”
Section: Ampkα1 Maintains Ros At Low Levels Through the Regulation Ofmentioning
confidence: 98%
“…As the standard chemotherapy regimens, FOLFOX and XELOX still play an irreplaceable role in the treatment of CRC in advanced stages. Oxaliplatin (OXA), a third-generation platinum drug, is a DNA-interacting agent that disrupts DNA replication and transcription and induces ROS production, promoting apoptosis [2] [3]. Although OXA improves the objective response and median overall survival rates, the main dose-limiting toxicity, peripheral sensory neuropathy and drug resistance still limit its widespread use.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of diagnosis, synchronous metastases can be found in almost 20-25% of patients with CRC, and the majority of patients with stage III disease have a poor prognosis within 5 years of diagnosis. The mainstream drugs used for advanced CRC include 5-fluorouracil, capecitabine, oxaliplatin, irinotecan, vascular endothelial growth factor (VEGF) antibody and epidermal growth factor receptor (EGFR) antibody, which may be used as a single agent or in combination in the first or secondary line of therapy (2,3). However, these therapies are limited in application due to their toxic and adverse effects.…”
Section: Introductionmentioning
confidence: 99%